Public value co-creation in living labs: Results from three case studies - Nathalie Haug; Ines Mergel (Administrative Sciences, 2021)
Living Labs - innovation units established to introduce new methods and approaches into public sector organizations - have received a lot of attention as methods for experimentation and open innovation practices in public sector organizations. However, little is known so far about how they co-create public value and which conditions influence these co-creation practices. Therefore, the research questions are: which organizational factors influence the process of public value co-creation and which outcomes and values are produced as a result? The research questions were answered by employing a qualitative research approach conducting semi-structured interviews with employees and participants of three living labs in Germany and Austria. The results show top-level support and lab leadership as the most important context factors. Living labs produce tangible and intangible outcomes. The tangible outcomes are the products developed within the lab, and the intangible outcomes are created by the interaction between the lab's participants. The main contributions are twofold: first, context factors are identified that lead to the success of co-creation processes within living labs. Second, the study contributes to the literature on public value because it is shown that participation in living labs itself leads to added value in addition to the tangible and intangible outcomes.
Keywords: 350; Austria; co-creation; Germany; living labs; public value